Heparin – Messias or Verschlimmbesserung?. (29th July 2021) - Swan, Dawn; Carrier, Marc; Lisman, Ton; Thachil, Jecko
Abstract: A heightened risk of thrombosis noted early on with the severe acute respiratory syndrome coronavirus 2 infection led to the widespread use of heparin anticoagulation in the coronavirus disease 2019 (COVID‐19) pandemic. However, reports soon started appearing in the literature where an apparent failure of heparin to prevent thrombotic events was observed in hospitalized patients with this viral infection. In this review, we explore the likely mechanisms for heparin failure with particular relevance to COVID‐19. We also explore the role of anti‐Xa assays and global hemostatic tests in this context. The current controversy of dosing heparin in this disease is detailed with some possible mechanistic reasons for anticoagulant failure. We hope that lessons learnt from the use of heparin in COVID‐19 could assist us in the appropriate use of this anticoagulant in the future.